Studi Literatur Integrasi Sistem Akuntansi Informasi dengan FinTech dan Open Banking : Inovasi Keuangan di Era Digital - Kenny Brighi Milala; Benaya.S Hutagalung; Muhammad Rafly Fachrezy; Ade Gunawan (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study focuses on examining the integration of Accounting Information Systems (AIS) with advances in financial technology (FinTech) and the concept of Open Banking in the context of financial sector innovation in the era of digital transformation. Through a qualitative research approach that relies on international and national academic literature studies from 2022 to 2025, this study examines various topics including accounting digitization, Computerized Accounting Information System (CAIS) frameworks, the Task-Technology Fit concept, blockchain implementation, FinTech ecosystem dynamics, and Open Banking regulations. The results of the study show that the integration of AIS with FinTech and Open Banking technologies can improve the effectiveness of transaction recording, facilitate direct financial reconciliation, and increase the level of transparency and accuracy of financial reports. However, this implementation faces significant obstacles in the form of information security issues, the absence of uniform API standards, varying levels of infrastructure readiness, and the need to adjust human resource capacity. This study emphasizes that to obtain optimal benefits, organizations need to implement API-based system architecture, strengthen data management, apply CAIS models according to the organizational context, and promote a regulatory framework that facilitates collaboration between regulators, banks, and FinTech service providers.